Prospects of dietary seaweeds and their bioactive compounds in sustainable poultry production systems: A symphony of good things? - Mlambo, Victor; Mnisi, Caven M.; Matshogo, Tumisang B.; Mhlongo, Godfrey (Frontiers in Animal Science, 2022)
Modern poultry production systems face numerous economic, environmental, and social sustainability challenges that threaten their viability and acceptability as a major source of animal protein. As scientists and producers scramble to find cost-effective and socially acceptable solutions to these challenges, marine macroalgae (seaweeds) are an ingenious option. Indeed, the incredible array of nutritive and bioactive compounds present in these macroscopic marine organisms can be exploited as part of sustainable poultry production systems of the future. Incorporating seaweeds in poultry diets could enhance feed utilization efficiency, growth performance, bird health, meat stability and quality, and consumer and environmental health. Theoretically, these benefits are mediated through the putative antiviral, antibacterial, antifungal, antioxidant, anticarcinogenic, anti-inflammatory, anti-allergic, antithrombotic, neuroprotective, hypocholesterolemic, and hypoglycemic properties of seaweed bioactive compounds. Despite this huge potential, exploitation of seaweed for poultry production appears to be constrained by a variety of factors such as high fibre, phenolics, and ash content. In addition, conflicting findings are often reported when seaweeds or their extracts are used in poultry feeding trials. Therefore, the purpose of this review paper is to collate information on the production, phytochemical components, and nutritive value of different seaweed species. It provides an overview of in vivo effects of dietary seaweeds as measured by nutrient utilization efficiency, growth performance, and product quality and stability in poultry. The utility of dietary seaweeds in sustainable poultry production systems is explored, while gaps that require further research are highlighted. Finally, opportunities that exist for enhancing the utility of seaweeds as a vehicle for sustainable production of functional poultry products for better global food and nutrition security are presented.